Hyaluronic Acid Gel With (HARRL) and Without Lidocaine (HAJU) for the Treatment of Moderate-to-Severe Nasolabial Folds: A Randomized, Evaluator-Blinded, Phase III Study - Fagien, Steven; Monheit, Gary; Jones, Derek; Bank, David; Sadick, Neil; Nogueira, Alessandra; Mashburn, Jay H (Dermatologic surgery, 2018)
Hyaluronic acid (HA) dermal fillers are frequently used to correct or smooth facial wrinkles and folds such as nasolabial folds. To compare the efficacy and safety of 2 HA gels, formulated by 2 different manufacturing processes: XpresHAn Technology (HARRL [with lidocaine]) and Hylacross technology (HAJU-a comparator product without lidocaine). One hundred seventy subjects with bilateral nasolabial folds rated as moderate or severe, according to the Wrinkle Severity Rating Scale (WSRS), received injections of HARRL in the nasolabial folds on one side of the face and HAJU on the other side. Investigator- and subject-assessed wrinkle severity was measured up to 48 weeks after final injection. HARRL exhibited a similar safety and efficacy profile compared with HAJU. Noninferiority of HARRL was demonstrated at 24 weeks (WSRS mean change from baseline mean difference -0.1 [95% confidence interval: -0.15, 0.01], p = .090). Incidence of adverse events was 40% for both treatments. HARRL exhibited a similar safety and efficacy profile compared with HAJU.